1973
DOI: 10.1097/00005650-197305000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Medical Care Utilization

Abstract: A multidimensional approach to the study of the factors that determine medical care utilization is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…In an earlier study of these samne two populations, a comparison of their appointment behavior in the total medical care system showed more variance between the two (24). It appears that members of the poverty population break fewer appointments for mental health clinic services than for other medical services, and that members of the general plan sample break more mental health appointments.…”
Section: Referral Patternsmentioning
confidence: 88%
“…In an earlier study of these samne two populations, a comparison of their appointment behavior in the total medical care system showed more variance between the two (24). It appears that members of the poverty population break fewer appointments for mental health clinic services than for other medical services, and that members of the general plan sample break more mental health appointments.…”
Section: Referral Patternsmentioning
confidence: 88%
“…Additionally, the attendance rates of scheduled preventative care visits is approximately 50% in adolescent patients 6. The reasons for this are varied but factors correlating with increased missed appointments include minority racial status,7 8 low socioeconomic class,711 younger age,8 9 10 prior missed appointments,7 larger family size,11 urban social setting,12 marital or family discord13 (as shown in online supplementary table S1) and residential instability 14…”
Section: Introductionmentioning
confidence: 99%
“…Studies of follow-up compliance in adult populations have been reported in the outpatient clinic setting [7][8][9][10][11] ; however, no studies have reported follow-up compliance after an ICU stay. Similarly, no studies of follow-up care after PICU stays have been reported.…”
mentioning
confidence: 99%